THE ANIMUS OF THE MAIN CHARACTER IN “GIRL MANS UP” NOVEL BY M-E GIRARD - Marceline, Florencia Sandra; Mandala, Robby Satria (Universitas Putera Batam, 2023)
This research is conducted to discover the animus of a masculine girl in the novel titled “Girl Mans Up” written by M-E Girard. This research applies an analytical psychology approach, specifically archetypal approach with the concept of animus archetype proposed by Carl Jung. Animus is the masculine qualities or traits in females’ psyche, in opposition with her outer appearance. This research focuses on the stages of the animus development of the main female character whose outer appearance was not feminine. The research method used is descriptive qualitative method. To collect and analyze the data, the researchers use library research method. There are two types of data, which are primary and secondary. Primary data are collected from the novel and secondary data are collected from books and articles related to animus to support the research. The analysis shows that the main character’s animus was on the first and second stage of development, with three data for Man of Power stage and six data for Man of Action stage, and that gender expression does not fully signify the person’s psychological traits.